A basis water quality monitoring plan for rehabilitation and protection - M. Enriquez; R. Tanhueco (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Safeguarding water resources became a major concern in many parts of the world as it aims to provide safe and healthy water for humans. Water quality monitoring is a popular tool in ensuring water quality is safe and within the allowable limits and standards for the health of the community. To provide interventions and strategies for the rehabilitation, a water quality monitoring plan was conducted to describe the water quality and the classification of the river.METHODS: This study conducted an environmental analysis to determine existing conditions and processes in the surrounding environment such as the land use, drainage pattern, reconnaissance survey of the river, and a key interview to describe the barangay profile and the community's water use and practices. The water quality monitoring covers the evaluation of ten water quality parameters: temperature, pH, dissolved oxygen, total dissolved solids, total suspended solids, phosphate, nitrate, oil and grease, chloride, and E. coli.FINDINGS: Results of the study presents the water quality against the ten water quality criteria. Phosphate measured on four stations ranges between 2.40-4.50 mg/L exceeding the allowable 0.50mg/L; the oil and grease exceeds the standards 2 mg/L with measured values of 2.40-4.60 mg/L in stations 2, 3, and 4; while measured chloride in all stations prove that the water is salty with values exceeding the freshwater requirement of 250mg/L; and the measured TSS in stations 2, 3 and 4 ranges from 32.30 to 49.3 mg/L exceeds the standards of 30mg/L.  E. coli was also detected in water samples collected in all sampling stations. The computed water quality index of 39.02 described water as poor, always impaired, and threatened by the surrounding environment.  CONCLUSION: The measured concentrations for phosphate, oil/ grease, chloride, and TSS exceeds the water quality requirement suggesting that the water is contaminated. The E. coli detected in all water samples, further recommends prohibition of recreational activities to avoid accidental intakes and skin contact on the polluted water.  The existing activities in the surrounding residential, commercial and agricultural areas contributed to water contamination as aggravated by the unreliable drainage system, absence of proper sanitation facilities, and collection and disposal behavior of the community. From this, a scientific basis can be drawn on how the river can be rehabilitated and protected and serve as guide for policymakers and water managers on implementing strategies to achieve sustainable water resources.